The influence of current density of deposition on Zn–Ni coatings properties - Wykpis, K.; Popczyk, M.; Niedbała, J.; Budniok, A.; Łągiewka, E. (Фізико-хімічна механіка матеріалів, 2011)
Zn–Ni coatings were deposited under galvanostatic conditions at current density in the range of 20 to 60 mA⋅cm⁻². The influence of current density of deposition on the surface morphology, chemical and phase composition and corrosion resistance was investigated. Structural investigations were performed by the X-ray diffraction (XRD) method. The surface morphology and chemical composition of deposited coatings were studied using a scanning electron microscope JEOL JSM-6480. Studies of general electrochemical corrosion resistance were carried out in the 5% NaCl, using potentiodynamic and electrochemical impedance spectroscopy (EIS) methods. Local corrosion resistance was determined by Scanning Kelvin Probe (SKP) method. On the ground of the research, the possibility of deposition of Zn–Ni coatings containing 14…18 at.% Ni was shown. It was stated, that surface morphology, chemical and phase composition of these coatings to a small extent, depend on the current density of deposition. However, current density of deposition determines the quantity of zinc which is co-deposited with nickel and is bounded in the form of an intermetallic compound or a solid solution. Small differences in chemical composition and the uneven distribution of the Zn(Ni) and Ni₂Zn₁₁ phases on coatings surface may cause differences in the local Kelvin potential. As a result, the Zn–Ni coatings exhibit corrosion resistance that varies depending on the deposition current density. The optimal values of current density for the sake of corrosion resistance are found to be j = 30 and 40 mA⋅cm⁻². Покрытия на основе системы Zn–Ni гальваностатически осаждены при плотности тока j = 20…60 mA⋅cm⁻². Исследовано влияние плотности тока осаждения на морфологию поверхности, химический и фазовый состав, а также коррозионную прочность. Для структурных экспериментов использован рентгенодифракционный метод (XRD). Морфологию поверхности и химический состав осажденного покрытия изучали на сканирующем электронном микроскопе JEOL JSM-6480, а коррозионную прочность – в 5%-ом растворе NaCl, применяя методы потенциодинамической поляризации и электрохимической импедансной спектроскопии (EIS). Локальная коррозионная прочность определена с помощью метода сканирующего зонда Кельвина (SKP). Показана возможность осаждения Zn–Ni с 14…18 at.% Ni. Выявлено, что морфология поверхности, химический и фазовый состав этих покрытий слабо зависят от плотности тока осаждения, которая, тем не менее, определяет количество цинка, осажденного вместе с никелем и связанного в форме интерметаллического соединения или твердого раствора. Незначительные отличия в химическом составе и неравномерное распределение фаз Zn(Ni) и Ni₂Zn₁₁ на поверхности покрытия могут обусловить отличия в значениях локального потенциала Кельвина. В результате коррозионная прочность покрытий на основе системы Zn–Ni изменяется в зависимости от плотности тока осаждения. Оптимальные значения плотности тока, при которых коррозионная прочность покрытий наиболее высокая, составляют j = 30 и 40 mA⋅cm⁻². Покриви на основі системи Zn–Ni гальваностатично осаджено за густини струму j = 20…60 mA⋅cm⁻². Досліджено вплив густини струму осадження на морфологію поверхні, хімічний та фазовий склад, а також корозійну тривкість. Для структурних випроб використано рентгенодифракційний метод (XRD). Морфологію поверхні та хімічний склад осадженого покриву вивчали на сканівному електронному мікроскопі JEOL JSM-6480, а корозійну тривкість – у 5%-му розчині NaCl, застосовуючи методи потенціодинамічної поляризації та електрохімічної імпедансної спектроскопії (EIS). Локальну корозійну тривкість визначено за допомогою методу сканівного зонда Кельвіна (SKP). Показано можливість осадження Zn–Ni із 14…18 at.% Ni. Встановлено, що морфологія поверхні, хімічний та фазовий склад цих покривів слабо залежать від густини струму осадження, яка, однак, визначає кількість цинку, що співосаджується з нікелем і зв’язаний у формі інтерметалічної сполуки або твердого розчину. Незначні відмінності у хімічному складі і нерівномірний розподіл фаз Zn(Ni) та Ni₂Zn₁₁ на поверхні покриву можуть спричинити відмінності у значеннях локального потенціалу Кельвіна. В результаті корозійна тривкість покривів на основі системи Zn–Ni змінюється залежно від густини струму осадження. Оптимальні значення густини струму, за яких корозійна тривкість покривів найвища, становлять j = 30 і 40 mA⋅cm⁻².